Development of Metacognition-Based LKPD to Improve Conceptual Understanding in Reaction Rate Material - Euis Nurmiati; Sugeng Bayu Wahyono; Muhammad Risal Rhomadan; Nurul Khairah; Ulfa Nabila Tafrienda (Postgraduate, University of Mataram, 2025)
The importance of constructivism-based chemistry learning is to develop students' conceptual understanding and metacognitive skills through active engagement, with the teacher as a facilitator, to create critical, independent, and globally competitive graduates. This study aims to develop Student Worksheets (LKPD) focused on metacognitive skills in learning reaction rate material, with the expectation of improving students' conceptual understanding and learning outcomes. Based on validation results, the LKPD has proven to be feasible for use, particularly in terms of language and metacognitive skills. In the first validation stage, the LKPD achieved an average percentage of 54.35%, which falls into the